2019
DOI: 10.1186/s13256-019-2195-4
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury due to high-output external biliary drainage in a patient with malignant obstructive jaundice: a case report

Abstract: Background Persistent high output is a rare but potentially serious complication of percutaneous biliary drainage. Case presentation A 68-year-old Sinhalese woman with a palliative self-expanding metal stent placed for an inoperable hilar cholangiocarcinoma presented with worsening obstructive jaundice. Ultrasonography showed intrahepatic duct dilatation with the self-expanding metal stent in situ . Since this was indicative of a blocked stent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…One of the earliest pieces of literature published byTaber et al in 1982 in the review of 120 cases showed 7 of the patients' daily biliary output exceeded average amount and only three exceeded outputs of more than 2 liters, as in our case demanding fluid resuscitation.2 In another case report published by Jayarajah et al mentioned development of high biliary output AKI in case of blocked SEMS and failure of internal catheterization requiring hemodialysis 6. Literature regarding percutaneous biliary procedure Nepal is limited, a study by Thapa A et al showed promising result in its role in palliation highlighting the need of further large scale study 4,7,8,9.…”
mentioning
confidence: 56%
“…One of the earliest pieces of literature published byTaber et al in 1982 in the review of 120 cases showed 7 of the patients' daily biliary output exceeded average amount and only three exceeded outputs of more than 2 liters, as in our case demanding fluid resuscitation.2 In another case report published by Jayarajah et al mentioned development of high biliary output AKI in case of blocked SEMS and failure of internal catheterization requiring hemodialysis 6. Literature regarding percutaneous biliary procedure Nepal is limited, a study by Thapa A et al showed promising result in its role in palliation highlighting the need of further large scale study 4,7,8,9.…”
mentioning
confidence: 56%
“…6 The other two relevant studies are single case reports -both presented patients with dehydration and AKI due to high external biliary drainage, and one showed the beneficial effects of octreotide application. 2,7 The other 18 articles were excluded because they were not describing excessive bile secretion or octreotide use.…”
Section: Discussionmentioning
confidence: 99%
“…Theirpatient showed spontaneous resolution of choleresis with supportive measures, although the moment when the amount of bile secretion began to decrease is unclear. 7 Tiruneh et al described the favorable effect of octreotide on choleresis, and its use was reasonable based on its physiological potential to inhibit bile secretion mediated by secretin. 2 The patient presented with high output biliary loss (3-4 liters a day) after the percutaneous biliary drainage for malignant obstruction of the distal common bile duct.…”
Section: Discussionmentioning
confidence: 99%
“…In 1990, a retrospective study revealed that 49% of patients with hepatoportal cholangiocarcinoma (HCCA)-associated OJ (130 cases) had developed acute renal failure[ 33 ]. The incidence of this complication ranges from 5% to 16%, and patient mortality rates were approximately 70%-80%[ 34 , 35 ].…”
Section: Pathophysiological Consequencesmentioning
confidence: 99%